Poéticas digitais : desafios contemporâneos para arte-educação - (:unkn) unknown (Universidade Estadual de Goiás, 2015)
The outburst of technology in contemporary art sprouted digital poetics , renewing visual creation, reshape the world view , create new forms of imaginary and iconic speeches, while that recodificam images of previous periods. Digital poetics are thus new iconography that put in crisis the various systems of representation and thereby open up new possibilities and challenges for the visual arts teaching. This work is a study that aims to investigate the potential of digital poetics in the field of art education , specifically in the visual arts education , from the development of digital poetics and aesthetics education in high school . It is intended to reflect about digital poetics and its constitution ; check how the digital poetics processes differ from other poetic ; discuss the principles of aesthetic education and art education in the context of cyberculture and analyze digital poetry produced by high school students , identifying the contribution of these to the visual arts education. The object of study consists of digital poetics and its implications for the visual arts education. We opted for a qualitative research with case study, based on conceptions of Lüdke and Andrew (1986), André (2013) and Chizzotti (2006). The theoretical framework that allows us to understand the theoretical and conceptual dimension of the problem studied account mainly with Rüdiger (2013), Jouve (2012), Santaella (2009, 2012), Vygotsky (1991.2009), Plaza and Tavares (1998) Barbosa (1998, 2010, 2012), Hernàndez (2000), Ostrower (2012), Rancière (2012) and Junior Duarte (2001). Data collection took place in a state school education network in the city of Buriti Alegre / Goiás, specifically with class 2nd year of high school. The instruments for data collection, guided by studies of Chizzotti (2006) and Andrew (2013), consisted of open questionnaire with students and conducting creative workshops. Data analysis was performed through the triangulation of them. The categories of analysis used solidified in five: a) interactivity; b) the aesthetic experience; c) creation; d) the expression and e) mediation. The analysis of students' productions within these categories showed that digital poetic cause double mediation, and cognitive and aesthetic, as potentiate the critical reception and allow both sensitive relations as the subject as intelligible world and with himself. The results indicate that develop activities with digital poetics in-class demand for adequate training of teachers room to make didactic mediation during the creation process of students with contemporary technologies,recognition of the potential that this type of artistic expression can bring to visual arts classes and the lives of students. It stands out among the challenges, the transformation of the mechanical attitude of the students in the production of images in aesthetic experience and didactic mediation necessary for the student looking to expand and become emancipated through contact with the digital poetics. These challenges can be overcome by the prioritization of aesthetic education, since this allows sensitive and intelligible relations with the images, whether of art or not, and thereby promotes the emancipation of the gaze of the student and modifies their relationship with technologies as means in the creation process.
Keywords: Cibercultura; Poéticas digitais; Educação estética; Arte-educação; ciberculture; Digital Poethics; Aesthetic education; Art education; CIENCIAS HUMANAS::EDUCACAO